New method of intelligent data transmission for IoV - Degan ZHANG; Pengzhen ZHAO; Jinxin GAO; Ting ZHANG; Changle GONG (物联网学报)
Internet of vehicle (IoV) is a hot research topic of the intelligent transportation,and the research of new method of the intelligent data transmission is one of the key technologies.In order to solve the problem of intelligent data transmission of IoV,a kind of new method which includes the important parameters such as vehicle density,vehicle speed,data transmission rate and data delay was proposed.By setting up network model of IoV and delaying function,the optimal routing method for intelligent data transmission which is based on Markovian decision theory was designed.Through comparison experiments with the relative methods show that the performance on improving the data transmission rate and shortening the delay of data transmission of IoV,it has important value for many applications of intelligent transportation with IoV,such as vehicle dynamic remote monitoring.